2000
DOI: 10.4049/jimmunol.164.8.4063
|View full text |Cite
|
Sign up to set email alerts
|

Differing Roles of Inflammation and Antigen in T Cell Proliferation and Memory Generation

Abstract: Recent studies have demonstrated that viral and bacterial infections can induce dramatic in vivo expansion of Ag-specific T lymphocytes. Although presentation of Ag is critical for activation of naive T cells, it is less clear how dependent subsequent in vivo T cell proliferation and memory generation are upon Ag. We investigated T cell expansion and memory generation in mice infected alternately with strains of Listeria monocytogenes that contained or lacked an immunodominant, MHC class I-restricted T cell ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 46 publications
3
55
1
Order By: Relevance
“…Inflammatory cytokine and chemokine secretion has been demonstrated in L. monocytogenes-infected tissues and the local cytokine milieu likely provides the exogenous stimuli that promote continued T cell division for 7-8 days following initial infection. In support of this, we have recently shown that increased expansion of activated T cells can be achieved by inflammation induced by a second bacterial infection in the absence of specific Ag (27). Whether IL-7 or IL-15 plays a role in promoting in vivo proliferation of L. monocytogenes-specific T lymphocytes during infection remains unknown and is currently being investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Inflammatory cytokine and chemokine secretion has been demonstrated in L. monocytogenes-infected tissues and the local cytokine milieu likely provides the exogenous stimuli that promote continued T cell division for 7-8 days following initial infection. In support of this, we have recently shown that increased expansion of activated T cells can be achieved by inflammation induced by a second bacterial infection in the absence of specific Ag (27). Whether IL-7 or IL-15 plays a role in promoting in vivo proliferation of L. monocytogenes-specific T lymphocytes during infection remains unknown and is currently being investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings that CD8 ϩ T cells (as well as NK cells) are induced to express IFN-␥ within 16 h after challenge with viable L. monocytogenes in vivo support this concept. Together, these data suggest that bystander cytokine activation of CD8 ϩ T cells may operate at several levels in contributing to host immunity: first, by providing an additional source of IFN-␥ during the early phase of response to infection; second, in expansion of effector T cells (46); and third, by nonspecifically maintaining the memory T cell pool (47). These results imply that prior antigenic experience provides the host not only with specific memory T cells, but a pool of cells, which collectively can contribute to innate immunity against subsequent unrelated infection.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to bacterial products and/or proinflammatory cytokines that promote the maturation of DCs to a highly stimulatory state for naive T cells or to the production of growth-promoting cytokines that drive CD8 ϩ T cell proliferation upon activation (20,25). We asked whether LM infection would alter the magnitude or kinetics of the CD8 ϩ T cell response to peptide-coated mature BMDCs.…”
Section: Cd8mentioning
confidence: 99%
“…ϩ T cell expansion kinetics can be affected by the inflammatory response to infection (25). This may be due to bacterial products and/or proinflammatory cytokines that promote the maturation of DCs to a highly stimulatory state for naive T cells or to the production of growth-promoting cytokines that drive CD8 ϩ T cell proliferation upon activation (20,25).…”
Section: Cd8mentioning
confidence: 99%